2002
DOI: 10.1176/appi.ajp.159.8.1265
|View full text |Cite
|
Sign up to set email alerts
|

Parental Depression: Animal Models of an Adverse Life Event

Abstract: Data from research on animal parenting reinforce the idea that parental mental illness may pose the first adverse life event for a child. A thorough risk-benefit assessment for the psychiatric care of parents of young children must consider the impact on the infant of exposure both to treatment and to parental illness. Preclinical data regarding the risk to offspring posed by untreated parental mental illness should be incorporated into clinical decision making in the treatment of parents with mental illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
96
0
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(111 citation statements)
references
References 277 publications
(236 reference statements)
8
96
0
4
Order By: Relevance
“…That is, MS rats exhibited decreased ambulatory activity and increased immobility in forced swim test, and spent significantly more time in the closed arms, less time in the open arms, of elevated plus maze, than NH rats. Our results are in accordance with reports by others following a similar separation paradigm (Ladd et al, 2000;Kalinichev et al, 2002;Newport et al, 2002;Daniels et al, 2004;Khoury et al, 2006), and further supports that neonatal maternal separation is an adequate rat model to study the molecular mechanism underlying the pathophysiology of affective disorders related with early life exposure to adverse events, including early parental neglect or loss, in human.…”
Section: Depression-and Anxiety-like Behaviors In Ms Ratssupporting
confidence: 93%
“…That is, MS rats exhibited decreased ambulatory activity and increased immobility in forced swim test, and spent significantly more time in the closed arms, less time in the open arms, of elevated plus maze, than NH rats. Our results are in accordance with reports by others following a similar separation paradigm (Ladd et al, 2000;Kalinichev et al, 2002;Newport et al, 2002;Daniels et al, 2004;Khoury et al, 2006), and further supports that neonatal maternal separation is an adequate rat model to study the molecular mechanism underlying the pathophysiology of affective disorders related with early life exposure to adverse events, including early parental neglect or loss, in human.…”
Section: Depression-and Anxiety-like Behaviors In Ms Ratssupporting
confidence: 93%
“…We recognize that several elements of this hypothesis were not directly measurable in the present study; e.g., we did not assess defensive responses after a metabolic stressor or psychosocial challenge and did not directly interrogate GR activity through methods such as dexamethasone suppression. However, their existence would be consistent with animal studies showing that signals from the social world can ''cue'' long-term alterations in HPA axis function, as well as other circuits in the endocrine, immune, and metabolic systems (7,9,10,13). These changes are thought to endow an animal with a defensive phenotype that is well suited to surviving in difficult social conditions (15,21).…”
Section: Discussionsupporting
confidence: 69%
“…One plausible answer to this question comes from the literature on the biological programming of early social experience (5)(6)(7). This work indicates that animals that receive inadequate parental nurturance or experience prolonged maternal separations can show permanent alterations in stress-related outflow of the autonomic nervous system (ANS) and the hypothalamicpituitary-adrenocortical (HPA) axis (8)(9)(10). These effects are partially mediated by diminished expression of and signaling by the glucocorticoid receptor (GR), a ligand-activated transcription factor that regulates HPA outflow through a hippocampal negative-feedback circuit (11,12).…”
mentioning
confidence: 99%
“…For example, a recent rodent study confirmed the hypothesis that diminished CRF receptor binding in the anterior pituitary is associated with a blunted ACTH response to CRF stimulation (Hauger et al, 2002). Preclinical data is certainly informative; however, its utility is limited by the incomplete homology of any animal model for the human condition (Newport et al, 2002).…”
Section: Discussionmentioning
confidence: 99%